Fc Binding by FcγRIIa Is Essential for Cellular Activation by the Anti-FcγRIIa mAbs 8.26 and 8.2 - Wines, Bruce D.; Trist, Halina M.; Esparon, Sandra; Impey, Rachael E.; Mackay, Graham A.; Andrews, Robert K.; Soares da Costa, Tatiana P.; Pietersz, Geoffrey A.; Baker, Ross I.; Hogarth, P. Mark (Frontiers in Immunology, 2021)
FcγR activity underpins the role of antibodies in both protective immunity and auto-immunity and importantly, the therapeutic activity of many monoclonal antibody therapies. Some monoclonal anti-FcγR antibodies activate their receptors, but the properties required for cell activation are not well defined. Here we examined activation of the most widely expressed human FcγR; FcγRIIa, by two non-blocking, mAbs, 8.26 and 8.2. Crosslinking of FcγRIIa by the mAb F(ab’)2 regions alone was insufficient for activation, indicating activation also required receptor engagement by the Fc region. Similarly, when mutant receptors were inactivated in the Fc binding site, so that intact mAb was only able to engage receptors via its two Fab regions, again activation did not occur. Mutation of FcγRIIa in the epitope recognized by the agonist mAbs, completely abrogated the activity of mAb 8.26, but mAb 8.2 activity was only partially inhibited indicating differences in receptor recognition by these mAbs. FcγRIIa inactivated in the Fc binding site was next co-expressed with the FcγRIIa mutated in the epitope recognized by the Fab so that each mAb 8.26 molecule can contribute three only interactions, one via the Fc and two via the Fab regions. When the Fab and Fc binding were thus segregated onto different receptor molecules receptor activation by intact mAb did not occur. Thus, receptor activation requires mAb 8.26 Fab and Fc interaction simultaneously with the same receptor molecules. Establishing the molecular nature of FcγR engagement required for cell activation may inform the optimal design of therapeutic mAbs.